Implementasi Pembiayaan Ultra Mikro Berdasarkan Prinsip Syariah di KSPPS BMT Purwakarta Amanah Sejahtera (PAS) - Sandi Jaelani; Imam Sucipto; Jalaludin Jalaludin (EKSISBANK (Ekonomi Syariah dan Bisnis Perbankan), 2020)
The purpose of this study is to determine the existing ultra-micro financing model in KSPPS BMT Purwakarta Amanah Sejahtera (PAS), and how to implement ultra-micro financing in KSPPS BMT Purwakarta Amanah Sejahtera (PAS). The type of research used is field research, while the approach used in this study is a descriptive-qualitative approach. There are two types of ultra-micro financing done at KSPPS BMT PAS, namely multi-item ultra-micro financing and multi-service ultra-micro financing. for multi-item ultra micro financing, using the Murabahah contract and its implementation is in accordance with DSN-MUI fatwa number 04 / DSN-MUI / IV / 2000 concerning Murabahah. Then for multi-service ultra micro financing using ijarah agreement in the form of wakalah, the implementation is in accordance with DSN-MUI fatwa number 09 / DSN-MUI / IV / 2000 concerning ijarah financing and DSN-MUI fatwa number 112 / DSN-MUI / IX / 2017 about the ijarah agreement. So that the implementation of ultra-micro financing in PAS BMT KSPPS is in accordance with DSN-MUI fatwa number 119 / DSN-MUI / II / 2918 regarding ultra-micro financing based on Islamic principles.